Treatment options for the direct reuse of reclaimed water in developing countries - Silva, Tamires Lima Da [UNESP]; Sánchez-Román, Rodrigo Máximo [UNESP]; Queluz, João Gabriel Thomaz [UNESP]; Pletsch, Talita Aparecida (Elsevier, 2020)
Reclaimed water may be defined as wastewater treated for a specific purpose. To be safely reused as reclaimed water, wastewater must receive adequate treatment to meet the quality requirements designed to minimize negative environmental impacts and to ensure the protection of public health. For developing countries, treatment methods that are expensive and/or complex to operate are not ideal due to local technical, financial, and managerial limitations. Thus, low-cost wastewater treatment technologies are often the best fits for developing nations. Nonetheless, low-cost wastewater treatment solutions are usually unable to treat wastewater for potable reuse due to the high quality required for this purpose. However, these technologies can efficiently treat wastewater for other purposes, such as irrigation. Irrigation with wastewater that has often not been properly treated or that remains untreated is already a common practice in many developing countries. Besides being a non-conventional water and nutrient resource for agricultural production, irrigation with untreated wastewater represents an epidemiologic risk to farms, consumers, and surrounding communities. Considering the importance of the development of applicable wastewater treatment options for developing countries in order to provide safe direct reuse of reclaimed water, this chapter will present three low-cost treatment solutions based on solar energy disinfection, phytoremediation, and a combination of biofiltration and solar energy disinfection. The wastewater treatment systems were designed to treat wastewater to the microbiological quality threshold recommended by the World Health Organization (WHO) for unrestricted irrigation (fecal coliform ≤ 1000 MPN/100 mL).
Keywords: Biofilter; Constructed wetland; Solar disinfection; Wastewater reuse